The meaning of “strength executive" in the Constitutional Court decision for the execution of fiduciary securities - Muslim, Shohib; Hadiyantina, Shinta; Mundzir, Hudriyah; Ayub, Zainal Amin (Legality : Jurnal Ilmiah Hukum, 2023)
Judicial decisions must have legal implications for relevant parties. PMK No. 2/PUU-XIX/2021 remains debatable between creditors and debtors because it seemingly weakens the protection of creditors' rights. Creditors cannot immediately carry out enforcement procedures that cut off the creditor's business flow because the position of the subject of fiduciary obligations is in the debtor's control, making it possible for disputes between debtors and creditors. This normative legal research was conducted using a philosophical, juridical approach covering statutory policies, conceptual and case approaches. PMK No. 2/PUU-XIX/2021 does not regulate creditor legal provisions in enforcing fiduciary securities, making it difficult for creditors to execute them. The Constitutional Court should decide to guarantee justice for all parties and provide a decision with clear content and sentence structure, so multiple interpretations will not occur. The execution of fiduciary securities during the Covid-19 pandemic should not be immediately carried out because the creditor had to follow the predetermined procedures.